Longitudinal Associations of Stroke With Cognitive Impairment Among Older Adults in the United States: A Population-Based Study - Wu, Xia; Fan, Li; Ke, Songqing; He, Yangting; Zhang, Ke; Yang, Shijun (Frontiers in Public Health, 2021)
Abstract Objective: To explore the longitudinal associations of stroke with cognitive impairment in older US adults. Method: The data used in this longitudinal analysis were extracted from the National Health and Aging Trends Study (NHATS) from 2011 to 2019. Univariate and multivariable Cox proportional hazards regression models were performed to estimate the longitudinal association of stroke with cognitive impairment. The multivariable model was adjusted by the demographic, physical and mental characteristics, and the complex survey design of NHATS was taken into consideration. Results: A total of 7052 participants with complete data were included. At the baseline, the weighted proportion of cognitive impairment was 19.37% (95%CI, 17.92%-20.81%) and the weighted proportion of the history of stroke was 9.81% (95%CI, 8.90%-10.72%). In univariate analysis, baseline stroke history was significantly associated with cognitive impairment in the future (hazard ratio, 1.746; 95%CI, 1.461-2.088), and the baseline cognitive impairment was significantly associated with future report of stroke (hazard ratio, 1.436; 95%CI, 1.088-1.896). In multivariable model, the stroke was also significantly associated with cognitive impairment (hazard ratio, 1.241; 95%CI, 1.011-1.522), however, the reverse association wasn’t significant (hazard ratio, 1.068; 95%CI, 0.788-1.447). After excluding the data from proxy respondents, in the sensitive analyses, the results remained unchanged. Conclusion: Older adults in the United States who suffered strokes are more likely to develop cognitive impairment as a result in the future compared to those who have not had strokes. However, the reverse association didn’t hold. Furthermore, the study suggests it’s necessary to screen and take early intervention for cognitive impairment in stroke survivors and prevent the incidence of stroke by modifying risk factors in the general population with rapidly growing older US adults.